Analisis Kemandirian Fiskal Dan Belanja Daerah Terhadap Kemiskinan Di Provinsi Papua - Endro Risdiyanto; Julius Ary Mollet; Halomoan Hutajulu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study analyzes fiscal independence and regional spending in accelerating poverty alleviation in Papua Province through a pro-poor growth path through a panel data model with 3 options, namely Pooled Least Square (PLS), Fixed Effect Model (FEM), and Random Effect Model (REM). In this approach, data processing is carried out by combining time series and cross-section data and the method used is Ordinary Least Square (OLS) on empirical data from 29 Regencies/Cities in Papua Province from 2010 to 2021. Increased regional fiscal independence capacity and regional spending has little impact on reducing poverty, especially in districts where access is difficult to reach. During that period, poverty in districts/cities in the province of Papua showed a good trend, although not significant. In addition, there was a tendency for the pattern of change in poverty to be in the opposite direction to shopping areas. Where the tendency of an increase in regional spending has an impact on reducing the percentage of poor people in districts/cities in the province of Papua during that period.